Non-Similar Analysis of MHD Ferro-Nanofluid Flow over an Exponential Stretching/Shrinking Sheet with Particle Effects - Iftekhar Yousuf, Md Sayeed; Alam, Jahangir; Murtaza, M.G.; Islam, Md Touhidul; Uddin, Md Jashim; Islam, Tasnim Ul; Elahia, Md Fazley (Archives of Thermodynamics, 2026)
Biomagnetic nanofluids have attracted considerable attention because of their potential applications in biomedical engineering, particularly in drug delivery, cancer therapy, and thermal management systems. In the present study, a nonsimilar analysis of biomagnetic blood-based nanofluid containing multiwalled carbon nanotubes over an exponential stretching/shrinking sheet is investigated. The model incorporates several important physical effects, including a transverse magnetic field, viscous dissipation, suction/injection, particle volume fraction, particle radius, and particle spacing during nanoparticle–blood interaction. The governing partial differential equations are transformed using nonsimilarity transformations and solved numerically through the local nonsimilarity technique with the bvp4c solver in MATLAB. The effects of the physical parameters on velocity, temperature distribution, skin friction coefficient and local Nusselt number are analysed in detail. The results indicate that increasing the magnetic field parameter, particle radius and nanoparticle volume fraction significantly reduces the velocity profile while enhancing the temperature distribution. Moreover, an increase in particle spacing improves both velocity and temperature profiles. Quantitatively, the heat transfer rate decreases by approximately 23.46% and 8.83% in the stretching and shrinking cases, respectively, when the nanoparticle volume fraction increases from 0 to 0.1. Moreover, the skin friction coefficient increases by approximately 24.15% and 23.9% with the increasing magnetic field strength, while increasing the particle radius from 1 to 2 reduces the skin friction coefficient by approximately 16.52% and 33.18% in the stretching and shrinking cases, respectively. These findings provide useful insights for the design and optimisation of biomagnetic nanofluid systems in biomedical and thermal engineering applications.